Integrating Kamoro Oral Literature into a Deep Learning Pedagogical Model to Strengthen Character Values in Language and Literature Education Students - Lefaan, Adolina Velomena; Widodo, Dhanu Priyo; The Selly, Orlando Antonio (Riwayat: Educational Journal of History and Humanities, 2025)
This study explores the integration of Kamoro oral literature into a deep learning pedagogical model to strengthen character values among undergraduate students in Language and Literature Education. Despite the richness of indigenous oral narratives in Papua, they are often excluded from formal education. This research addresses the gap by investigating how Kamoro storiesrich in moral, ecological, and communal valuescan enhance students ethical awareness and cultural identity through a structured learning process. The research employed a qualitative descriptive method with an ethnographic orientation. Data were collected five months through in-depth interviews with Kamoro elders, classroom observations, student reflection journals, and semi-structured interviews with students and lecturers. Thematic analysis was used to identify core values embedded in the narratives and evaluate student engagement across five stages of deep learning: engagement, exploration, explanation, elaboration, and evaluation. Findings revealed that Kamoro oral literature contains strong cultural values such as respect for elders, environmental harmony, and communal responsibility. Students demonstrated meaningful engagement, critical thinking, and creative synthesis throughout the learning process. Reflective journals showed increased cultural pride and internalization of moral values. The inclusion of indigenous elders as co-educators also contributed to a more authentic and transformative learning experience. The study concludes that integrating indigenous oral traditions into deep learning frameworks not only enriches educational content but also supports character formation and cultural affirmation.